Color stability of three provisional dental materials submerged in two pigmenting agents - Chuquiano Bringas, Samantha Ysabel (2021)
Objective: To determine the color stability of three provisional dental materials when immersed in two pigment agents. Materials and methods: it is an experimental, analytical, prospective and longitudinal study. A total of 270 discs 15 mm in diameter and 1 mm thick were made with 3 temporary dental materials: bisacrylic resin (Luxatemp Star) color A1, acrylic resin (Alike) color 59 and PMMA self-curing (Vitalloy) color 59 being submerged 30 of each sample in purple corn, coffee and distilled water (control). Color readings are used initially, at 7 and 28 days using the VITA® EasyShade® V spectrophotometer with the CIELab system. Results: The acrylic resin presented greater color stability compared to the bisacrylic resin and PMMA self-curing (p <0.01). The coffee presented the greatest color change (p <0.001). After 28 days of storage, there was a color change in all the materials analyzed. Conclusion: Acrylic resin has  the highest color stability. The coffee caused the greatest color change and the immersion's time was decisive for the color stability.